BODIES , BODIES DOCILE AND HOMOSEXUALITY: A FILM REVIEW OF SENHORITAS EM UNIFORME (Fiep Bulletin - online, 2016)
Ladies in Uniform (1931) is a German pioneer lesbian film portraying a boarding school for military's daughters in which is applied the order and authority that cannot be challenged and is rooted in strict discipline, working on the creation of what Foucault called docile bodies, ie, useful and obedient subjects. Within such an environment freedom is restricted, the students have leisure activities that were identified as appropriate for women at the time, such as singing, dancing and theater and dare a little in the discovery of body image and the development of the body, but a student makes the most courageous act, challenging the rules and daring to get involved romantically with one of her teachers and so, the purpose of the survey is to unravel the film discourse on homosexuality. To this end, it is grounded on the semiotic analysis and the thought of Charles Sanders Peirce about the object, sign and interpreter and uses the film analysis model Structural/Significant proposed by Antonio Moreno in "A Personagem Homossexual no Cinema Brasileiro" (1995). The theoretical basis is taken from the book "Now You See It. Studies on Lesbian and Gay Film" (1990) from Richard Dyer, allowing it to theoretically substantiate the analysis of the film. After is done the qualification of the speech content in relation to the homosexual characters, it is possible to arrive to the conclusion that the movie contributes to a positive image of lesbian sexuality as it portrays this as natural.
Keywords: Cinema; Lesbian; Ladies in Uniform.